2010
DOI: 10.1152/ajpheart.00488.2009
|View full text |Cite
|
Sign up to set email alerts
|

Role of nitric oxide as a key mediator on cardiovascular actions of atrial natriuretic peptide in spontaneously hypertensive rats

Abstract: The objective was to study atrial natriuretic peptide (ANP) effects on mean arterial pressure (MAP) and cardiovascular nitric oxide (NO) system in spontaneously hypertensive rats (SHRs), investigating the receptors and signaling pathways involved. In vivo, SHRs and Wistar-Kyoto (WKY) rats were infused with saline (0.05 ml/min) or ANP (0.2 microg.kg(-1).min(-1)) for 1 h. MAP and nitrites and nitrates excretion (NOx) were determined. NO synthase (NOS) activity and endothelial (eNOS), neuronal (nNOS) and inducibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
5
11
0
Order By: Relevance
“…Our results have shown that the renal effects of ANP would be mediated, at least in part, by interaction with the NO system in this genetic model of hypertension, as shown previously with regard to the cardiovascular effects of the peptide in SHR (6). In addition, we have demonstrated that ANP infusion augmented renal NOS activity in SHR, without modifying its expression.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Our results have shown that the renal effects of ANP would be mediated, at least in part, by interaction with the NO system in this genetic model of hypertension, as shown previously with regard to the cardiovascular effects of the peptide in SHR (6). In addition, we have demonstrated that ANP infusion augmented renal NOS activity in SHR, without modifying its expression.…”
Section: Resultssupporting
confidence: 87%
“…NOS blockade blunted the ANP hypotensive effect in both groups, but L-NAME treatment had a more marked impact on normotensive ones. These results confirm our previous findings indicating that the NO system is involved in the hypotensive effect induced by ANP and that this response is impaired in hypertensive animals (6,9). Thus our results suggest that ANP's hypotensive effects involve different mechanisms in SHR and in WKY, indicating that the NO system plays a more Table 4 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nishikimi T et al have demonstrated, in mice, that ANP has antifibrotic effects on the kidney, involving the activation of NPR-A and/or C-type natriuretic peptide receptor (NPR-C), producing an increase in renal cGMP levels and a decrease in transforming growth factor beta (TGF-β) expression and collagen I and III content [7]. Further, in our laboratory we provided evidence that ANP exerts a hypotensive effect through enhancement of cardiovascular and renal NOS activity, in both, normotensive and hypertensive rats [810]. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that ANP interacts with NPR-C in atria, ventricles, and the aorta to activate Ca 2+ -loaded calmodulin and endothelial nitric oxide synthase (eNOS) through the Gi protein [12]. In particular, impairment of the eNOS response to ANP has been observed in SHR as compared to normotensive WKY, thus suggesting that dysfunctions in the NPR-C signaling pathway, which leads to the reduced NO availability, may contribute to the maintenance of hypertension in SHR [13]. Musclin-induced increase in the concentration of intracellular calcium was observed in the widely used cultured vascular cells A7r5 [14].…”
Section: Discussionmentioning
confidence: 99%